Dampak Konsumen Terhadap Pinjaman Online (PINJOL) - Muhammad Ramli; Mulono Apriyanto; Ali Azhar; Feni Puspitasari; KMS. Novyar Satriawan Fikri (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2023)
According to the findings, inhabitants of the Indragiri Hilir region have a strong understanding of the procedures involved in applying for loans online if their income is at least comparable to the average pay. This is the case regardless of whether or not they live in the region. People who earn less than their drinking wages have a low level of understanding, but those who earn more than their drinking wages have a very high level of knowledge. Those people who make more than their drinking wages are able to understand more. According to these findings, respondents who identify as either single or married have a grasp of online loans that is, on average, superior to that of other respondents. This holds true for both of the categories that were previously discussed. The respondents' decision to utilise this online loan application was most influenced by the fact that it was convenient to borrow money without having to offer a guarantee; however, providing financial support to members of the borrower's family was only a secondary factor in the decision to utilise this online loan application.